Scenario-based simulation and debriefing sessions can potentially improve non-technical skills in nurse anesthetist students of Iran; A quasi-experimental study - Ali Khalafi; Pegah Arman; Nahid Manouchehrian (Elsevier, 2022)
Background: Technical skills refer to all practical abilities necessary for surgery or anesthesia. Non-technical skills (Task management, Team-working, Situation-awareness, and Decision-making) are abilities accelerate the individuals' adaptability in critical anesthetic situations. Simulation (a type of unreal simulated education similar to the real situation in which the learner can achieve clinical experiences using human models) and debriefing sessions (a method of education in which the learners have a discussion about what they have learned during simulation) are educational protocols for non-technical skills improvement. Thus, in the current quasi-experimental study, we aimed to investigate the effects of scenario-based simulation and debriefing sessions on the development of non-technical skills among nurse anesthetist students (Hamadan, Iran). Methods: Nurse anesthetist students (n = 60) were categorized into control (n = 30) and test (n = 30) groups. Anesthesia induction was simulated by an anesthesiologist for students in a practice hall. Immediately, debriefing sessions were held to improve non-technical skills. A week later, the Anaesthetists' Non-Technical Skills (ANTS) checklist was hired, and non-technical skills were scored. Collected data were analyzed (SPSS v.16.0) and represented as Mean ± SD. P-value < 0.05 was also considered a significant level. Results: Significantly (p < 0.05), following simulation and debriefing interventions, non-technical skills were improved, including Task management (mean ANTS score: 11.13 ± 2.87 and 14.53 ± 2.20 in control and test, respectively), Team-working (mean ANTS score: 10.42 ± 3.20 and 14.93 ± 2.19 in control and test, respectively), and Situation-awareness (mean ANTS score: 9.62 ± 4.30 and 13.20 ± 2.86 in control and test, respectively) skills. Besides, Decision-making skills represented no significant (p = 0.299) alteration after the intervention (mean ANTS score: 5.81 ± 2.75 and 4.73 ± 2.55 in control and test, respectively). Conclusions: Scenario-based simulation training and debriefing sessions, as the proposed educational curriculum, can promote non-technical skills during anesthesia induction in nurse anesthetist students leading to improvement of patient safety and prevention of medical profession errors.